Rancangan Sistem Tracking Kendaraan Airside Berbasis IoT dengan GPS-LoRa dan Fitur Peringatan Dini di UPBU Kelas III Maimun Saleh - lulu salsitiara (Universitas Lampung, 2026)
This study aims to design an IoT-based airside vehicle tracking system using GPS and LoRa technology at UPBU Class III Maimun Saleh Airport. The system is developed to monitor vehicle position, speed, and movement in real-time. An early warning feature is implemented to detect overspeed and geofence violations in restricted areas. The system integrates GPS modules, LoRa communication, and a web-based monitoring interface. The results show that the system is able to provide accurate positioning data and real-time monitoring, thereby improving operational safety and efficiency in airport airside areas.